TLR9 is dispensable for intestinal ischemia/reperfusion-induced tissue damage - Slone, Emily Archer; Pope, Michael R.; Roth, Mary R.; Welti, Ruth; Fleming, Sherry D. (My University, 2013)
The mortality rate due to intestinal ischemia/reperfusion (IR) remains at 60-80%. As toll-like receptor (TLR) 4 has been shown to be critical for IR injury in several organs, including the intestine, and TLR9 is necessary for IR-induced damage of the liver, we investigated the hypothesis that TLR9 is involved in intestinal IR-induced damage. Wildtype (C57Bl/6) and TLR9[superscript -/-] mice were subjected to intestinal IR or Sham treatment. Several markers of damage and inflammation were assessed, including mucosal injury, eicosanoid production, cytokine secretion and complement deposition. Although IR-induced injury was not altered, PGE[subscript 2] production was decreased in TLR9[superscript -/-] mice. Attenuated PGE[subscript 2] production was not due to differences in percentage of lipids or COX-2 transcription. The data indicate that TLR9 is not required for IR-induced injury or inflammation of the intestine.
Keywords: Mouse; Intestine; Complement; TLRs; Ischemia